Kenneth Arrow's fundamental critique of neoclassical economics - Yam Maayan (Duke University, Center for the History of Political Economy (CHOPE), 2024)
The paper presents Kenneth Arrow's interpretation of the competitive general equilibrium model, arguing he used it to articulate an ambitious critique of what he called the 'neoclassical theory.' Without arguing that Arrow's account of neoclassical theory was correct, I explore how Arrow was 'thinking with' this model, trying to reshape economic analysis. In particular, Arrow reinterpreted this model as a 'normative ideal' that should be used by contemplating the ways the world differs from it. I clarify this suggestion by showing how Arrow employed it to achieve three interrelated goals: (1) de-constructing the image of the self-regulating market (2) introducing new fundamental 'building blocks' for economic models, (3) providing an analytical reference point for a unified economic perspective. In the end, I explain why while 'Arrow's critique' genuinely aimed at deconstructing what Arrow identified as the orthodox view it did not suggest an alternative paradigm.
Keywords: 330; economic thought; Neoclassical economics; general equilibrium theory; Kenneth Arrow; Economic Methodology